Factors Influencing the Accuracy of Freehand Implant Placement: A Prospective Clinical Study - Sigmar Schnutenhaus; Marie Wagner; Cornelia Edelmann; Ralph G. Luthardt; Heike Rudolph (MDPI AG, 2021)
(1) Background: The objective of implant prosthetic restoration is to ensure the best possible rehabilitation of function and esthetics. Optimal positioning of the implant with regard to the bone availability, surrounding soft tissue, and prosthetic sustainability should be strived for during implant placement. The factors influencing freehand implant placement and the accuracy achieved with this procedure are investigated in this prospective clinical study. (2) Methods: Implants were placed in the single-tooth edentulous sites of the premolar and molar areas in 52 patients. Three-dimensional (3D)-planning was performed virtually prior to the freehand implant operation, and the desired position of the implant was provided to the surgeon. (3) Results: The deviations between the planned and the actually achieved position with freehand implant placement showed the following mean values and standard deviations: angle 8.7 ± 4.8°, 3D deviation at the implant shoulder 1.62 ± 0.87 mm, mesiodistal deviation 0.87 ± 0.75 mm, buccolingual deviation 0.70 ± 0.66 mm, and apiocoronal deviation 0.95 ± 0.61 mm. The type of jaw had a significant influence on accuracy. Major deviations were observed in the lower jaw. Furthermore, the timing of implant placement influenced the mesiodistal deviation and angular deviation; (4) Conclusions: Freehand implant placement demonstrated a higher level of deviation between the planned and actually achieved implant positions. In particular, the ranges showed a large spread. From a prosthetic point of view, there may be complications during the restoration of the prosthetic crown if the implant exit point is not optimally located or if the implants show a high angular deviation.